The Role of Women in Rural Development in Enugu State, Nigeria - Nnamdi, Aguene Ignatius (International Journal of Sustainable Development & World Policy, 2020)
The study examined the implication of lack of women empowerment and non-membership of organization in rural development in Nigeria. Specifically, the study investigated whether empowering women economically can increase their participation in rural development and whether women who belong to organizations contribute more to rural development projects more than those who do not belong to organizations. The ex-post survey method was adopted and 17 Local Government Councils in Enugu State were sampled. The respondents include 507 females and 458 males who were purposively selected from the sample areas through a multi-state sampling technique. Structured questionnaire was administered to elicit the desired responses. Data collected were processed through an econometric method that involves descriptive and inferential statistics. Findings from the study showed that women’s rights much more than men’s are routinely ignored and infringed upon at different stages of their lives despite constitutional guarantees. The study found that awareness campaign was the most influential factor motivating women to participate in community development and therefore should be encouraged. The study also found that membership of co-operative societies was a mobilizing factor in community development. Based on these findings, the study recommended amongst others, that women education should be encouraged to empower more women to contribute to rural development in Nigeria.